Marine Breakwater Simulator using 3D Printing and Stereo Vision - Yu., Sunjin; Sung Kim, Kyung (International Journal of Engineering and Technology, 2018)
Background/Objectives: Breakwaters are widely used to reduce the risk of waves. In this paper, we propose a marine breakwater simulator using 3D printer and Stereo Camera.Methods/Statistical analysis: The proposed system can be divided into three parts. First, we create a virtual wave generator to create the breakwater effect. Next, a buoy with 3D printing technology is made to measure the water height. Finally, we use visual sensors to track our buoys.Findings: We use 3D printing technology to create custom buoys and use them in simulators. Therefore, customized buoys can be 3D printed to match the simulator situation. The custom buoy is designed to be easily tracked from the vision sensors. We use color and shape information to track the buoy. First, candidate regions of the buoy are extracted using color information. Next, the shape fitting technique finds the location of the real buoy among the candidate areas of the buoy. Finally, we use the Kalman filter to keep track of the position of the buoy. In this paper, we attempt to shift from the existing marine breakwater research using large equipment or virtual space to the study of measuring the actual height of actual waves. We have improved the function of the ocean breakwater simulator by using computer vision technology.Improvements/Applications: The proposed wave generation simulator can generate virtual waves and simulate wave danger and wave risk protection by measuring wave height using 3D printing and vision technology.Â
Keywords: 3D Printing; Stereo Vision; Breakwater; Simulator; Kalman Filter.